PENGARUH IKLIM ORGANISASI DAN REMUNERASI TERHADAP MOTIVASI DAN KEPUASAN KERJA PARAMEDIS DI RUMAH SAKIT UMUM PURI HUSADA TEMBILAHAN KABUPATEN INDRAGIRI HILIR (Jurnal Tepak Manajemen Bisnis, 2014)
In this paper aims to determine the effect of Organizational Climate on Motivation and Job Satisfactionin General Hospital Paramedic PuriHusadaTembilahan Indragiri Hilir.To determine the effect of remunerationon Motivation and Job Satisfaction in General Hospital Paramedic PuriHusadaTembilahan Indragiri Hilir.Toinvestigate factors Organizational Climate, Motivation and Remuneration of the Job Satisfaction in GeneralHospital ParamedicPuriHusadaTembilahan Indragiri Hilir. ReflitaInfluence of Organizational Climate and TheRemuneration of Motivation and Job Satisfaction Paramedics Public Hospital DistrictPuriHusadaTembilahanIndragiri downstream. Samples will be taken at 100 paramedics. Probability samplingwith stratified sampling technique that samples taken by stratification or by reference to a certain extent, inorder to obtain a representative sample.Data analysis has been intended to assess and determine the relationship between the independent variable (X)that is leadership and motivation to the dependent variable(Y) that job satisfaction and performance of employeesat Puri Husada Hospital of Tembilahan. In analyzing and interpreting the data, descriptive analysis method andverification of analysis methods. Descriptive analysis method is used to describe the characteristics of respondentsand research variables, while the verification method used to test the research hypotheses by using relevantstatistical tests. While the verification method used in this study is path analysis (path analysis).The empirical results show that there is significant relationship between organizational climate on motivationParamedic Work on General Hospital PuriHusadaTembilahan Indragiri Hilir. Then based on hypothesis testingfound that a significant difference between the remuneration of the Paramedic Work motivation in the GeneralHospital PuriHusadaTembilahan Indragiri Hilir. Furthermore Based on the results of hypothesis testing foundthat there is significant relationship between organizational climate to satisfaction of Paramedic Work onGeneral Hospital PuriHusadaTembilahan Indragiri Hilir.Keywords : Climate Organization and Remuneration Of Motivation And Job Satisfaction